Design and construction of a new biosynthetic pathway for the production of curcuminoids in Escherichia coli - Rodrigues, Joana Lúcia Lima Correia (2012)
Curcuminoids are produced by plants and due to their potential as novel cancer-fighting drugs they have recently attracted increased attention. Nevertheless, they have a poor bioavailability. Cellular uptake is low, and they are quickly metabolized once inside the cell, requiring repetitive oral doses to achieve sufficient concentration inside the cell for therapeutic activity. The goal of this PhD project is to engineer a synthetic pathway for curcuminoid in a model bacterium and trigger its release concurrent with ultrasound treatment. The proposed tasks involve several design and engineering steps to program Escherichia coli to execute the new synthetic pathway triggered by a temperature increase. The heat shock response machinery of E. coli will be used as a sensor in the design of the model bacterium. Afterwards, the gene sequences of the enzymes that catalyze each reaction in the curcuminoid pathway will be synthesized and introduced in the E. coli genome applying several cloning strategies. Data from several well documented experiments on E. coli in relevant conditions that have been published were analyzed to select the most expressed heat shock genes in E. coli with the strongest heat shock promoters. The ibpA, dnaK and fxsA gene promoters were chosen based on their induction rates and expression and were validated by RT-qPCR and subsequently through the construction of a stress probe using an adequate reporter gene.